Analysis Violation of Professional Ethics in Manipulation Report Finance (Study The case of PT Garuda Indonesia) - Mufidatur Rohmah; Sri Trisnaningsih (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2023)
Everyone around the world is talking about the financial statement manipulation scandal. One of the many fraud or manipulation scandals in Indonesia's financial statements that has caught the public's attention is that of PT Garuda Indonesia. The purpose of this research is to analyze the professional ethics violated by the accountants of PT Garuda Indonesia when manipulating or falsifying financial statements. This study employs a case study approach and a qualitative research method at PT Garuda Indonesia. The data collection technique uses the literary method, namely searching for or digging various types of information related to violations of professional ethics in manipulating financial reports sourced from several types of literature originating from research journals, books, articles, and electronic media. Integrity, objectivity, competence, professional due care, and professional behavior are the principles of accounting ethics that were found to have been violated in this study.